THE EFFECT OF POSTCOLONIAL LITERARY STUDIES ON STUDENTS' HISTORICAL AWARENESS AND PERSPECTIVES TOWARD CULTURAL DIVERSITY - Bima Prana Chitra; Zuindra; Lisna Sari Siregar; Febianti Ngongo; Widelya Shafa April (Universitas Harapan Medan, 2026)
This study aimed to examine the effect of postcolonial literary studies on undergraduate students' historical awareness and their perspectives toward cultural diversity in higher education. The research employed a quantitative approach supported by qualitative evidence to obtain a comprehensive understanding of both the instructional process and its educational outcomes. Twenty undergraduate students from the English Literature Study Program participated in the study. Data were collected through Likert-scale questionnaires, classroom observations, semi-structured interviews, and students' reflective journals. The data were analyzed using descriptive statistics, instrument validity and reliability testing, and analyses of relationships among the research variables based on the proposed conceptual framework. The descriptive findings indicated that, prior to the instructional intervention, students demonstrated a moderate level of historical awareness with a mean score of 59.65, while their perspectives toward cultural diversity were categorized as moderately positive, with a mean score of 64.40. Throughout the learning process, students showed improved ability to connect literary texts with colonial history, understand the construction of cultural identities, and develop more inclusive attitudes toward cultural diversity. Classroom discussions centered on postcolonial literary texts encouraged critical reflection on power relations, cultural representation, and the continuing influence of colonial legacies in contemporary society. The findings suggest that postcolonial literary studies have considerable potential as an effective pedagogical approach for strengthening historical literacy, promoting intercultural understanding, and fostering inclusive perspectives among university students. This study contributes to the development of literary pedagogy, literature-based history education, and multicultural education within higher education institutions.